Optimization of Productive Zakat and Waqf as Islamic Social Finance Instruments in Indonesia - Ahmad Muhajir Algadri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the factors influencing the adoption and usage behavior of digital waqf platforms by integrating the Theory of Reasoned Action (TRA). Using a quantitative approach with 280 respondents and Structural Equation Modeling (SEM), the research examines the roles of subjective norms, technology advancement, and trust in shaping users’ attitudes, behavioral intentions, and actual usage. The findings show that all three antecedent variables significantly and positively influence attitude, which in turn increases behavioral intention, while behavioral intention strongly predicts usage behavior. Trust emerges as the most influential factor, emphasizing the importance of transparency, security, and Sharia compliance within digital waqf systems. These results contribute to the literature on Islamic philanthropic technology adoption and provide practical implications for waqf institutions to enhance digital literacy, strengthen system credibility, and improve technological innovation to increase public participation in digital waqf.